A salt-fog resistant composite film system based on chalcogenide glass and preparation method thereof

By plating the composite film system of the M1 film layer and the DLC film layer on the sulfur-based glass substrate, the problem of poor adhesion of the surface film layer of the sulfur-based glass is solved, the hardness and adhesion are improved, and the film system is maintained in harsh environments stability and low reflectivity.

CN116589200BActive Publication Date: 2025-02-14ZHONGSHAN JILIAN PHOTOELECTRIC TECH CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310369430.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-07
Publication Date
2025-02-14
Estimated Expiration
2043-04-07

AI Technical Summary

Technical Problem

The adhesion of the sulfur-based glass surface film layer is poor, and film defiling is prone to occur, and the prior art is difficult to maintain the stability and high transmittance of the film system in harsh environments.

Method used

The new material M1 was developed by co-evaporation technology, and the first germanium film layer, zinc sulfide film layer, second germanium film layer, M1 film layer, and third germanium film layer were sequentially plated on a sulfur-based glass substrate through physical vapor deposition technology. and the DLC film layer to form a salt spray-resistant composite film system.

Benefits of technology

The surface hardness of sulfur-based glass is improved, the adhesion of the film layer is enhanced, the film removal problem is solved, and the film layer is firm under salt spray, high and low temperatures and friction are maintained, achieving low reflectivity in the 8-12μm band. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116589200B_ABST
    Figure CN116589200B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of optical thin films, and relates to a salt-fog resistant composite film system with chalcogenide glass as a substrate and a preparation method. The present invention provides a salt-fog resistant composite film system with chalcogenide glass as a substrate, which includes a first germanium film layer, a zinc sulfide film layer, a second germanium film layer, an M1 film layer, a third germanium film layer and a DLC film layer in sequence from the chalcogenide glass substrate, wherein the M1 film layer is a mixed film layer obtained by co-evaporating zinc sulfide and ferrofluoride by physical vapor deposition technology. The composite film system of the present invention solves the problem of poor adhesion of the film layer on the surface of the chalcogenide glass, improves the surface hardness, and simultaneously achieves anti-reflection and protection effects, and improves the environmental resistance and optical properties of the chalcogenide glass.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of optical films, and relates to a salt-fog resistant composite film system with chalcogenide glass as a substrate and a preparation method thereof. Background Art

[0002] In recent years, infrared detection systems have been widely used in military and civilian fields. As an important protective component of the entire optical system, the performance of infrared window lenses often determines the service life of the optical system. Chalcogenide glass is an excellent athermal optical element with a small refractive index temperature coefficient. It can be made into aspheric or free-form surfaces using precision molding technology, which can improve the image quality of optical instruments while reducing the number of lenses in the system. In addition, molding technology has high production efficiency and can reduce manufacturing costs.

[0003] Chalcogenide glass itself has certain defects, such as low hardness, large thermal expansion coefficient and low softening point, which makes it easy to peel off the film when depositing the film on the chalcogenide glass, and due to the limitation of the thickness of the DLC film layer, the film structure does not match. Therefore, the film coated on the chalcogenide glass is required to have high transmittance and adapt to harsh environments.

[0004] At present, although there are many methods for preparing anti-reflection and protective films on the surface of chalcogenide glass, they are basically in the laboratory research and development stage. When used for mass production, the process conditions are demanding. Defective products often occur, and the reasons for the defects cannot be found, resulting in unstable production. Summary of the invention

[0005] In order to solve the above problems, the present invention provides a method for coating a dielectric film and a DLC composite film with chalcogenide glass as a substrate, and develops a new material M1 by using co-evaporation technology to match the film structure, thereby solving the problem of poor adhesion of the film layer on the surface of the chalcogenide glass and improving the surface hardness, while achieving anti-reflection and protection effects, and improving the environmental resistance and optical properties of the chalcogenide glass.

[0006] Specifically, in one aspect, the present invention provides a salt fog resistant composite film system based on chalcogenide glass, wherein the composite film system includes a first germanium film layer, a zinc sulfide film layer, a second germanium film layer, an M1 film layer, a third germanium film layer and a DLC film layer in order from the chalcogenide glass substrate, wherein the M1 film layer is a mixed film layer obtained by co-evaporating zinc sulfide and ferrofluoride by physical vapor deposition technology. Figure 1 A schematic diagram of the composite membrane system design structure of the present invention is shown.

[0007] More specifically, co-evaporating zinc sulfide and ferrofluoride by physical vapor deposition techniques includes co-evaporating zinc sulfide by barrier evaporation and depositing ferrofluoride by an electron gun.

[0008] More specifically, the first germanium film layer, the zinc sulfide film layer, the second germanium film layer and the third germanium film layer are plated by physical vapor deposition technology. The specific physical vapor deposition technology for plating the germanium film layer and the zinc film layer is not limited, which can be conventionally selected by those skilled in the art according to specific practices. Similarly, when evaporation is performed using physical vapor deposition technology to plate each film layer, the evaporation rate can be conventionally selected by those skilled in the art according to specific practices. For example, germanium can be evaporated using an electron beam at an evaporation rate of 0.1-0.5nm / s (for example, including 0.1, 0.2, 0.3, 0.4 and 0.5nm / s), and zinc sulfide can be evaporated using a resistive evaporation method at an evaporation rate of 0.6-1.0nm / s (for example, including 0.6, 0.7, 0.8, 0.9 and 1.0nm / s).

[0009] More specifically, in the deposition of the M1 film, the evaporation rate of ytterbium fluoride is 0.5-0.6 nm / s, and the evaporation rate of zinc sulfide is 0.5-0.6 nm / s.

[0010] More specifically, the thickness of the first germanium film layer, the zinc sulfide film layer, the second germanium film layer, the M1 film layer and the third germanium film layer is not limited, which can be conventionally selected by those skilled in the art according to specific practices, for example, the thickness of each film layer can be designed using film system design software. As an illustrative example, the thickness of the first germanium film layer, the zinc sulfide film layer, the second germanium film layer, the M1 film layer and the third germanium film layer can be designed so that the composite film system of the present invention can achieve anti-reflection in the 8-12 μm band. More specifically, as an illustrative example, the thickness of the first germanium film layer, the zinc sulfide film layer, the second germanium film layer, the M1 film layer and the third germanium film layer can be designed to be 170-175nm (e.g., 172.76nm), 280-285nm (e.g., 281.9nm), 660-670nm (e.g., 665.15nm), 155-160nm (e.g., 157.21nm) and 145-155nm (e.g., 150nm), respectively. More specifically, the composite film system of the present invention can achieve an average reflectivity of less than 6% for the 8-12 μm band (including, for example, an average reflectivity of 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, and 5.5%). More specifically, the composite film system of the present invention can achieve an average reflectivity of 5% for the 8-12 μm band. More specifically, the composite film system of the present invention can achieve an average reflectivity of 1.5% for the 8-12 μm band.

[0011] More specifically, during the physical vapor deposition process, the temperature of the chalcogenide glass substrate is 70-100° C. More specifically, when germanium and zinc sulfide film layers are prepared on the chalcogenide glass, the substrate baking temperature is 80° C.

[0012] More specifically, the DLC film layer is deposited by chemical vapor deposition technology. The method of depositing the DLC film layer by chemical vapor deposition technology is well known in the art and can be routinely selected by those skilled in the art according to specific practices.

[0013] More specifically, during the chemical vapor deposition process, the chalcogenide glass substrate is not subjected to a heating treatment.

[0014] More specifically, the initial vacuum degree of the evaporation coating layer is 1.0×10 -4 Pa~2.0×10 -3 Pa.

[0015] More specifically, the thickness of the DLC film layer is less than 1000 nm. More specifically, the thickness of the DLC film layer may be 100-980 nm. More specifically, the thickness of the DLC film layer may be 950 nm.

[0016] In another aspect, the present invention provides a method for preparing a salt-fog resistant composite film system based on chalcogenide glass, the method comprising the following steps:

[0017] 1) Clean the chalcogenide glass substrate,

[0018] 2) sequentially depositing a first germanium film layer, a zinc sulfide film layer and a second germanium film layer on the surface of the chalcogenide glass substrate by physical vapor deposition technology,

[0019] 3) Co-evaporating zinc sulfide and ferrite fluoride to form an M1 film layer on the second germanium film layer by physical vapor deposition technology,

[0020] 4) depositing a third germanium film layer on the M1 film layer by physical vapor deposition technology, and

[0021] 5) A DLC film layer is plated on the third germanium film layer by chemical vapor deposition technology.

[0022] More specifically, the cleaning in step 1) includes an ion-assisted cleaning process.

[0023] More specifically, the co-evaporation of zinc sulfide and ferrofluoride by physical vapor deposition in step 3) includes co-evaporation by barrier evaporation of zinc sulfide and electron gun deposition of ferrofluoride.

[0024] The specific physical vapor deposition technology for coating the germanium film layer and the zinc film layer is not limited, and this can be conventionally selected by those skilled in the art according to specific practices. Similarly, when evaporation is performed using physical vapor deposition technology to coat each film layer, the evaporation rate can be conventionally selected by those skilled in the art according to specific practices. For example, germanium can be evaporated using an electron beam at an evaporation rate of 0.1-0.5 nm / s (for example, including 0.1, 0.2, 0.3, 0.4 and 0.5 nm / s), and zinc sulfide can be evaporated using a resist evaporation method at an evaporation rate of 0.6-1.0 nm / s (for example, including 0.6, 0.7, 0.8, 0.9 and 1.0 nm / s).

[0025] More specifically, when evaporating the M1 material, the rate of ytterbium fluoride is 0.5-0.6 nm / s, and the rate of zinc sulfide is 0.5-0.6 nm / s.

[0026] More specifically, the thickness of the first germanium film layer, the zinc sulfide film layer, the second germanium film layer, the M1 film layer and the third germanium film layer is not limited, which can be conventionally selected by those skilled in the art according to specific practices, for example, the thickness of each film layer can be designed using film system design software. As an illustrative example, the thickness of the first germanium film layer, the zinc sulfide film layer, the second germanium film layer, the M1 film layer and the third germanium film layer can be designed so that the composite film system of the present invention can achieve anti-reflection in the 8-12 μm band. More specifically, as an illustrative example, the thickness of the first germanium film layer, the zinc sulfide film layer, the second germanium film layer, the M1 film layer and the third germanium film layer can be designed to be 170-175nm (e.g., 172.76nm), 280-285nm (e.g., 281.9nm), 660-670nm (e.g., 665.15nm), 155-160nm (e.g., 157.21nm) and 145-155nm (e.g., 150nm), respectively. More specifically, the composite film system of the present invention can achieve an average reflectivity of less than 6% for the 8-12 μm band (including, for example, an average reflectivity of 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, and 5.5%). More specifically, the composite film system of the present invention can achieve an average reflectivity of 5% for the 8-12 μm band. More specifically, the composite film system of the present invention can achieve an average reflectivity of 1.5% for the 8-12 μm band.

[0027] More specifically, during the physical vapor deposition process, the temperature of the chalcogenide glass substrate is 70-100° C. More specifically, when germanium and zinc sulfide film layers are prepared on the chalcogenide glass, the substrate baking temperature is 80° C.

[0028] More specifically, the method of coating a DLC film layer by chemical vapor deposition technology is well known in the art and can be routinely selected by those skilled in the art according to specific practices.

[0029] More specifically, during the chemical vapor deposition process, the chalcogenide glass substrate is not subjected to a heating treatment.

[0030] More specifically, the thickness of the DLC film layer is less than 1000 nm. More specifically, the thickness of the DLC film layer may be 100-980 nm. More specifically, the thickness of the DLC film layer may be 950 nm.

[0031] More specifically, in the method, the initial vacuum degree is set to 1.0×10 -4 Pa~2.0×10 -3 Pa.

[0032] More specifically, in the method, when the initial vacuum degree reaches 1.0×10 -4 Pa~2.0×10 -3 When 250 Å / s, the chalcogenide glass substrate is cleaned with an ion-assisted process and then the film is deposited.

[0033] Beneficial effects of the present invention

[0034] The present invention solves the problems of poor film firmness, easy film removal, poor reliability and difficulty in large-scale use when depositing infrared thin films on chalcogenide glass. The present invention uses a special film structure design, process optimization, and research and development of new mixed materials to deposit a film structure on a chalcogenide glass substrate, which has the following advantages:

[0035] (1) The DLC protective layer improves the surface hardness of the chalcogenide glass;

[0036] (2) The introduction of M1 material adjusts the stress matching of the film layer and optimizes the process, greatly improving the adhesion of the film layer and solving the problem of film peeling on the surface of chalcogenide glass;

[0037] (3) The film layer can pass reliability testing tests such as salt spray, high and low temperature, and friction.

[0038] The present invention also successfully deposits an 8-12 μm band anti-reflection protective film on a chalcogenide glass substrate, achieving an average reflectivity of 5% for the 8-12 μm anti-reflection protective film. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 A schematic diagram of the membrane system design structure of the present invention is shown.

[0040] Figure 2 The designed spectrum curve of the film system of the present invention is shown.

[0041] Figure 3 The actual test spectrum curve of the film system of the present invention is shown.

[0042] Figure 4The sample surface image after environmental testing of the film system sample of the present invention is shown. DETAILED DESCRIPTION

[0043] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0044] Embodiment 1:

[0045] This embodiment provides a salt fog resistant composite film system based on chalcogenide glass, which is prepared as follows:

[0046] (1) In the typical chalcogenide glass IG2(Ge 33 As 12 Se 55 , refractive index 2.4967@10μm), the film system design software is used to optimize the design of 8-12μm anti-reflection film, the theoretical design spectrum curve is as follows Figure 2 As shown, the average reflectivity is 1.5%, and the specific film design structure is: the first layer is germanium, and the film thickness is 172.76nm; the second layer is zinc sulfide, and the film thickness is 281.9nm; the third layer is germanium, and the film thickness is 665.15nm; the fourth layer is M1, and the film thickness is 157.21nm; the fifth layer is germanium, and the film thickness is 150nm; the sixth layer is DLC, and the film thickness is 950nm.

[0047] (2) The first five layers of dielectric films were deposited using a 1350 vacuum optical coating machine, which was equipped with a 6-position crystal control probe, a 6-position resist, a single e-type electron gun, and a Kaufman ion source. The vacuum system consisted of a mechanical pump and a cold pump. The DLC film was deposited using an LWT700-VI RF plasma chemical vapor deposition deposition equipment, which was equipped with an RF power supply and a vacuum system consisting of a mechanical pump and a molecular pump.

[0048] (3) Before coating the film, the chalcogenide glass substrate needs to be wiped to avoid scratches, residual moisture and dust that may cause the deposited film to be unstable, and then treated with a wiping cloth dipped in the following reagents: alcohol-acetone-alcohol-polishing liquid-alcohol-acetone.

[0049] (4) Place the wiped substrate on the public tray, evacuate the equipment, set the temperature to 85°C, and when the initial vacuum reaches 2.0×10 -3 Pa, the substrate is cleaned by an ion source for 5 minutes to clean the substrate surface and increase the ion activity on the substrate surface.

[0050] (5) Germanium is evaporated by electron beam at a rate of 0.3 nm / s. Zinc sulfide is evaporated by barrier evaporation at a rate of 0.8 nm / s. When evaporating M1 material, the rate of ytterbium fluoride is 0.5 nm / s and the rate of zinc sulfide is 0.5 nm / s.

[0051] (6) After the above film coating is completed, when the temperature cools down to below 70°C, the chalcogenide glass substrate can be placed in the chemical vapor deposition equipment and vacuum pumping is started. When the vacuum degree reaches 5×10 -3 Pa, RF power was 400W, constant pressure mode was 3Pa, 35SCCM argon was filled, and the substrate was cleaned for 300S. When the vacuum degree was 3×10 -3 pa, the RF power is 600W, the reaction gas is methane, argon is used as the carrier gas, the ratio is CH4:Ar=149:10, the vacuum pressure is 10Pa, and the deposition time is 2800S. After the preparation is completed, cool for 20 minutes, take out the substrate, and complete the preparation of the protective film.

[0052] (7) The spectral reflectance curve of 8-12 μm was measured using a PerkinElmer Spectrum 3 infrared spectrometer. Figure 3 As shown, the average reflectivity is 5%.

[0053] Environmental testing of the film:

[0054] The performance of the film layer is tested by the film firmness, salt spray, high and low temperature, and friction tests in the GBJ2485-1995 standard test.

[0055] Film firmness: Use 3M tape with a width of 20mm and an adhesion of (10±1)N / 25mm to quickly pull it up vertically at 90° without any film falling off, meeting the use requirements.

[0056] Salt spray: Using HY-60 salt spray test box, the temperature is 35±2℃, the concentration is 4.9%~5.1%, and the pH is 6.5~7.2. Sodium chloride solution is sprayed continuously for 24 hours. The film layer has no defects such as peeling, delamination, cracks, bubbles, etc., which meets the use requirements.

[0057] High and low temperature: Put the coated sheet into a high and low temperature test box, keep it at -60℃ and 70℃ for two hours respectively, take it out and put it at room temperature, visually inspect it and use tape to test its firmness. There is no peeling, cracks or bubbles in the film layer, and no film shedding is found after tape adhesion and pulling, which meets the use requirements.

[0058] Friction: To protect the film surface, super strong friction is adopted. An external rubber friction head is tied to the friction tester, and it is pressed on the film surface with a force of 0.196N. After rubbing for 1000 turns, there is no scratch or other damage on the film surface, which meets the use requirements.

[0059] After testing, the sample surface Figure 4 shown.

[0060] Example 2

[0061] This embodiment provides a salt fog resistant composite film system based on chalcogenide glass, which is prepared as follows:

[0062] (1) In the typical chalcogenide glass IG2(Ge 33 As 12 Se 55 , refractive index 2.4967@10μm), the film design software is used to optimize the design of 8-12μm anti-reflection film, the theoretical average reflectivity is 1.5%, the specific film design structure: the first layer is germanium, the film thickness is 172.76nm; the second layer is zinc sulfide, the film thickness is 281.9nm; the third layer is germanium, the film thickness is 665.15nm, the fourth layer is M1, the film thickness is 157.21nm, the fifth layer is germanium, the film thickness is 150nm; the sixth layer is DLC, the film thickness is 950nm.

[0063] (2) The first five layers of dielectric films were deposited using a 1350 vacuum optical coating machine, which was equipped with a 6-position crystal control probe, a 6-position resist, a single e-type electron gun, and a Kaufman ion source. The vacuum system consisted of a mechanical pump and a cold pump. The DLC film was deposited using an LWT700-VI RF plasma chemical vapor deposition deposition equipment, which was equipped with an RF power supply and a vacuum system consisting of a mechanical pump and a molecular pump.

[0064] (3) Before coating the film, the chalcogenide glass substrate needs to be wiped to avoid scratches, residual moisture and dust that may cause the deposited film to be unstable, and then treated with a wiping cloth dipped in the following reagents: alcohol-acetone-alcohol-polishing liquid-alcohol-acetone.

[0065] (4) Place the wiped substrate on the public tray, evacuate the equipment, set the temperature to 85°C, and when the initial vacuum reaches 1.0×10 -4 Pa, the substrate is cleaned by an ion source for 5 minutes to clean the substrate surface and increase the ion activity on the substrate surface.

[0066] (5) Germanium is evaporated by electron beam at a rate of 0.4 nm / s, zinc sulfide is evaporated by barrier evaporation at a rate of 1.0 nm / s, and when evaporating M1 material, ytterbium fluoride is evaporated at a rate of 0.6 nm / s and zinc sulfide is evaporated at a rate of 0.6 nm / s.

[0067] (6) After the above film coating is completed, when the temperature cools down to below 70°C, the chalcogenide glass substrate can be placed in the chemical vapor deposition equipment and vacuum pumping is started. When the vacuum degree reaches 5×10 -3 Pa, RF power was 400W, constant pressure mode was 3Pa, 35SCCM argon was filled, and the substrate was cleaned for 300S. When the vacuum degree was 3×10 -3 pa, the RF power is 600W, the reaction gas is methane, argon is used as the carrier gas, the ratio is CH4:Ar=149:10, the vacuum pressure is 10Pa, and the deposition time is 2800S. After the preparation is completed, cool for 20 minutes, take out the substrate, and complete the preparation of the protective film.

[0068] (7) The spectral reflectance curve of 8-12 μm was tested using a PerkinElmer Spectrum 3 infrared spectrometer, and the average reflectance was 5%.

[0069] Environmental testing of the film:

[0070] The performance of the film layer is tested by the film firmness, salt spray, high and low temperature, and friction tests in the GBJ2485-1995 standard test.

[0071] Film firmness: Use 3M tape with a width of 20mm and an adhesion of (10±1)N / 25mm to quickly pull it up vertically at 90° without any film falling off, meeting the use requirements.

[0072] Salt spray: Using HY-60 salt spray test box, the temperature is 35±2℃, the concentration is 4.9%~5.1%, and the pH is 6.5~7.2. Sodium chloride solution is sprayed continuously for 24 hours. The film layer has no defects such as peeling, delamination, cracks, bubbles, etc., which meets the use requirements.

[0073] High and low temperature: Put the coated sheet into a high and low temperature test box, keep it at -60℃ and 70℃ for two hours respectively, take it out and put it at room temperature, visually inspect it and use tape to test its firmness. There is no peeling, cracks or bubbles in the film layer, and no film shedding is found after tape adhesion and pulling, which meets the use requirements.

[0074] Friction: To protect the film surface, super strong friction is adopted. An external rubber friction head is tied to the friction tester, and it is pressed on the film surface with a force of 0.196N. After rubbing for 1000 turns, there is no scratch or other damage on the film surface, which meets the use requirements.

[0075] Comparative Example 1

[0076] This comparative example provides a salt spray resistant composite film system based on chalcogenide glass, which is prepared as follows:

[0077] (1) In the typical chalcogenide glass IG2(Ge 33As 12 Se 55 , refractive index 2.4967@10μm), the film design software is used to optimize the design of 8-12μm anti-reflection film, the theoretical average reflectivity is 2.0%, the specific film design structure: the first layer is germanium, the film thickness is 172.76nm; the second layer is zinc sulfide, the film thickness is 281.9nm; the third layer is germanium, the film thickness is 665.15nm, the fourth layer is zinc sulfide, the film thickness is 157.21nm, the fifth layer is germanium, the film thickness is 150nm; the sixth layer is DLC, the film thickness is 950nm.

[0078] (2) The first five layers of dielectric films were deposited using a 1350 vacuum optical coating machine, which was equipped with a 6-position crystal control probe, a 6-position resist, a single e-type electron gun, and a Kaufman ion source. The vacuum system consisted of a mechanical pump and a cold pump. The DLC film was deposited using an LWT700-VI RF plasma chemical vapor deposition deposition equipment, which was equipped with an RF power supply and a vacuum system consisting of a mechanical pump and a molecular pump.

[0079] (3) Before coating the film, the chalcogenide glass substrate needs to be wiped to avoid scratches, residual moisture and dust that may cause the deposited film to be unstable, and then treated with a wiping cloth dipped in the following reagents: alcohol-acetone-alcohol-polishing liquid-alcohol-acetone.

[0080] (4) Place the wiped substrate on the public tray, evacuate the equipment, set the temperature to 85°C, and when the initial vacuum reaches 2.0×10 -3 Pa, the substrate is cleaned by an ion source for 5 minutes to clean the substrate surface and increase the ion activity on the substrate surface.

[0081] (5) Germanium is evaporated by electron beam at a rate of 0.3 nm / s. Zinc sulfide is evaporated by barrier evaporation at a rate of 0.8 nm / s. When evaporating M1 material, the rate of ytterbium fluoride is 0.5 nm / s and the rate of zinc sulfide is 0.5 nm / s.

[0082] (6) After the above film coating is completed, when the temperature cools down to below 70°C, the chalcogenide glass substrate can be placed in the chemical vapor deposition equipment and vacuum pumping is started. When the vacuum degree reaches 5×10 -3 Pa, RF power was 400W, constant pressure mode was 3Pa, 35SCCM argon was filled, and the substrate was cleaned for 300S. When the vacuum degree was 3×10 -3 pa, the RF power is 600W, the reaction gas is methane, argon is used as the carrier gas, the ratio is CH4:Ar=149:10, the vacuum pressure is 10Pa, and the deposition time is 2800S. After the preparation is completed, cool for 20 minutes, take out the substrate, and complete the preparation of the protective film.

[0083] Environmental testing of the film:

[0084] The performance of the film layer is tested by the film layer firmness test in the GBJ2485-1995 standard test, where

[0085] Film firmness: When a 3M tape with a width of 20 mm and an adhesion of (10±1) N / 25 mm was quickly pulled up vertically at 90°, the film peeled off and could not meet the use requirements. This proves that the introduction of the M1 film material can improve the film adhesion and solve the problem of film peeling on the surface of chalcogenide glass.

[0086] Comparative Example 2

[0087] This comparative example provides a salt spray resistant composite film system based on chalcogenide glass, which is prepared as follows:

[0088] (1) In the typical chalcogenide glass IG2(Ge 33 As 12 Se 55 , refractive index 2.4967@10μm), the film design software is used to optimize the design of 8-12μm anti-reflection film, the theoretical average reflectivity is 1.5%, the specific film design structure: the first layer is germanium, the film thickness is 172.76nm; the second layer is zinc sulfide, the film thickness is 281.9nm; the third layer is germanium, the film thickness is 665.15nm, the fourth layer is M1, the film thickness is 157.21nm, the fifth layer is germanium, the film thickness is 150nm; the sixth layer is DLC, the film thickness is 950nm.

[0089] (2) The first five layers of dielectric films were deposited using a 1350 vacuum optical coating machine, which was equipped with a 6-position crystal control probe, a 6-position resist, a single e-type electron gun, and a Kaufman ion source. The vacuum system consisted of a mechanical pump and a cold pump. The DLC film was deposited using an LWT700-VI RF plasma chemical vapor deposition deposition equipment, which was equipped with an RF power supply and a vacuum system consisting of a mechanical pump and a molecular pump.

[0090] (3) Before coating the film, the chalcogenide glass substrate needs to be wiped to avoid scratches, residual moisture and dust that may cause the deposited film to be unstable, and then treated with a wiping cloth dipped in the following reagents: alcohol-acetone-alcohol-polishing liquid-alcohol-acetone.

[0091] (4) Place the wiped substrate on the public tray, evacuate the equipment, set the temperature to 85°C, and when the initial vacuum reaches 2.0×10 -3 Pa, the substrate is cleaned by an ion source for 5 minutes to clean the substrate surface and increase the ion activity on the substrate surface.

[0092] (5) Germanium is evaporated by electron beam at a rate of 0.3 nm / s. Zinc sulfide is evaporated by barrier evaporation at a rate of 0.8 nm / s. When evaporating M1 material, the rate of ytterbium fluoride is 0.4 nm / s and the rate of zinc sulfide is 0.6 nm / s.

[0093] (6) After the above film coating is completed, when the temperature cools down to below 70°C, the chalcogenide glass substrate can be placed in the chemical vapor deposition equipment and vacuum pumping is started. When the vacuum degree reaches 5×10 -3 Pa, RF power was 400W, constant pressure mode was 3Pa, 35SCCM argon was filled, and the substrate was cleaned for 300S. When the vacuum degree was 3×10 -3 pa, the RF power is 600W, the reaction gas is methane, argon is used as the carrier gas, the ratio is CH4:Ar=149:10, the vacuum pressure is 10Pa, and the deposition time is 2800S. After the preparation is completed, cool for 20 minutes, take out the substrate, and complete the preparation of the protective film.

[0094] Environmental testing of the film:

[0095] The performance of the film layer was tested by the film layer firmness, salt spray, high and low temperature, and friction tests in the GBJ2485-1995 standard test. The salt spray, high and low temperature, and abrasion resistance tests all met the use requirements, but the film layer firmness was weakened compared to Example 1, proving that the material composition and plating process of the M1 film layer are complementary and indispensable.

[0096] In the description of the specification, the description with reference to the terms "one embodiment", "specific embodiment", "example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0097] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the described specific implementation schemes or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A salt spray resistant composite film system based on chalcogenide glass, characterized in that: The composite film system includes a first germanium film layer, a zinc sulfide film layer, a second germanium film layer, an M1 film layer, a third germanium film layer and a DLC film layer in sequence from a chalcogenide glass substrate, wherein the M1 film layer is a mixed film layer obtained by co-evaporating zinc sulfide and ytterbium fluoride through physical vapor deposition technology, and the M1 film layer is used to match the film system structure; the composite film system achieves an average reflectivity of 5% in the 8-12 μm band.

2. The composite film system according to claim 1, characterized in that: In the plating of the M1 film layer, the evaporation rate of ytterbium fluoride is 0.5-0.6 nm / s, and the evaporation rate of zinc sulfide is 0.5-0.6 nm / s.

3. The composite film system according to claim 1, characterized in that: The first germanium film layer, the zinc sulfide film layer, the second germanium film layer and the third germanium film layer are plated by physical vapor deposition technology.

4. The composite film system according to claim 1, characterized in that: Co-evaporating zinc sulfide and ytterbium fluoride by physical vapor deposition techniques includes co-evaporating zinc sulfide by barrier evaporation and depositing ytterbium fluoride by electron gun.

5. The composite film system according to claim 1, characterized in that: The DLC film is deposited by chemical vapor deposition technology.

6. The composite membrane system according to any one of claims 1 to 5, characterized in that: The initial vacuum degree of the evaporation coating layer is 1.0×10 -4 Pa~2.0×10 -3 Pa.

7. The composite film system according to claim 1, characterized in that: The thickness of the DLC film layer is less than 1000 nm.

8. A method for preparing a salt-fog resistant composite film system based on chalcogenide glass, characterized in that: The method comprises the following steps: 1) Clean the chalcogenide glass substrate, 2) sequentially depositing a first germanium film layer, a zinc sulfide film layer and a second germanium film layer on the surface of the chalcogenide glass substrate by physical vapor deposition technology, 3) Co-evaporating zinc sulfide and ytterbium fluoride on the second germanium film layer by physical vapor deposition technology to form an M1 film layer, 4) depositing a third germanium film layer on the M1 film layer by physical vapor deposition technology, and 5) A DLC film layer is plated on the third germanium film layer by chemical vapor deposition technology, and the composite film system achieves an average reflectivity of 5% in the 8-12 μm band.

9. The method according to claim 8, characterized in that The co-evaporation of zinc sulfide and ytterbium fluoride by physical vapor deposition in step 3) includes co-evaporation by barrier evaporation of zinc sulfide and deposition of ytterbium fluoride by electron gun.

10. The method according to claim 8, characterized in that The cleaning in step 1) includes an ion-assisted cleaning process, In the plating of the M1 film, the evaporation rate of ytterbium fluoride is 0.5-0.6nm / s, and the evaporation rate of zinc sulfide is 0.5-0.6nm / s. The initial vacuum degree of the evaporation coating layer is 1.0×10 -4 Pa~2.0×10 -3 Pa, The thickness of the DLC film layer is less than 1000 nm.

Citation Information

Patent Citations

  • Preparation method of large-size infrared optical element low-stress protection antireflection film

    CN114774847A